Duplication of inferior vena cava- case report of an anatomic variation - Abdulrazzaq, Saad Mohammed; Abdel Wahab, Emad Mohamad Nafie (2019)
Introduction:The inferior vena cava (IVC) is the largest vein in human being draining the blood from the lower part of the body running along the right side of the abdominal aorta. Double IVC is a rare congenital anomaly with an incidence of 0.2%–3%. Materials and Methods:This case of double IVC was observed during dissection of the abdomen of an adult male cadaver in the dissection hall of Anatomy, Faculty of Medicine, International Islamic University Malaysia. We report the presence of normal IVC on the right side with a left sided one seen running parallel to it. This left sided IVC starts at the junction of the left internal and external iliac vein dorsal to the left common iliac artery at the level of fifth lumbar vertebra. It joins the right IVC ventrally to the abdominal aorta at the level of first lumbar vertebra by connecting venous anastomosis. The left suprarenal vein drains to this connecting part between the right and left IVC. Discussion and conclusion: Double IVC is relatively uncommon and can prolong smoothly without any adverse consequences abnormalities, but in some situations such as retroperitoneal surgery, vascular interventional procedures, placement of IVC filters and various surgical / radiological techniques, the study of the anatomy of these variations is of crucial importance.